2000
DOI: 10.1021/ac990986z
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Identification of Peptides from Gel-Isolated Membrane Proteins Using a Microfabricated Device for Combined Capillary Electrophoresis/Nanoelectrospray Mass Spectrometry

Abstract: The coupling of microfabricated devices to nanoelectrospray mass spectrometers using both a triple quadrupole and a quadrupole time-of-flight mass spectrometer (QqTOF MS) is presented for the analysis of trace-level membrane proteins. Short disposable nanoelectrospray emitters were directly coupled to the chip device via a low dead volume connection. The analytical performance of this integrated device in terms of sensitivity and reproducibility was evaluated for standard peptide mixtures. A concentration dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 41 publications
3
138
0
1
Order By: Relevance
“…First, microfabrication robustness and reproducibility make available reliable micro-and nanospray emitters, with automation possibilities [21]. Second, the design flexibility provided by microfabrication allows the integration of different analytical processes on the same microfluidic device prior to delivery to the mass spectrometer, such as sample preparation [22][23][24], analyte separation [25][26][27], proteolytic digestion [9,28], or even integration of the whole process [29].…”
mentioning
confidence: 99%
“…First, microfabrication robustness and reproducibility make available reliable micro-and nanospray emitters, with automation possibilities [21]. Second, the design flexibility provided by microfabrication allows the integration of different analytical processes on the same microfluidic device prior to delivery to the mass spectrometer, such as sample preparation [22][23][24], analyte separation [25][26][27], proteolytic digestion [9,28], or even integration of the whole process [29].…”
mentioning
confidence: 99%
“…Xem xét sự xuất hiện của các protein chỉ thị bệnh rất cần thiết trong quá trình chuẩn đoán, đặc biệt là chuẩn đoán sự có mặt của bệnh ở giai đoạn sớm và theo dõi sự tiến triển của bệnh để có thể áp dụng hướng điều trị hợp lý, tăng cường hiệu quả điều trị bệnh, nhờ đó bệnh nhân sớm hồi phục trở lại và kéo dài sự sống. Ngày nay, có nhiều protein chỉ thị bệnh đã được phát hiện, trở thành các chỉ tiêu xét nghiệm sinh hóa quan trọng không thể thiếu trong chuẩn đoán lâm sàng đối với hội chứng mạch vành cấp như: Hs-CRP (High-sensitivity C-reactive protein), BNP (Brain natriuretic peptide, B-type natriuretic peptide), NT-proBNP (N-terminal pro-BNP), CK-MB (Creatine kinasemyocardial bland), troponin… Tuy nhiên, hệ protein trong huyết thanh người hết sức đa dạng và phức tạp, trong đó chỉ tính riêng 22 loại protein có hàm lượng cao nhất đã chiếm đến 99% lượng protein tổng số [14]. Các protein này gây nhiều khó khăn cho quá trình nghiên cứu các protein có hàm lượng thấp và chính các protein có hàm lượng thấp này mới thực sự có nhiều ý nghĩa trong nghiên cứu sinh học và y học [1].…”
Section: Mở đầUunclassified
“…Most reports on MCE-ESI-MS have focused on developing designs for facile interfacing of microfabricated devices with MS. [92][93][94]113,[126][127][128][129][130][131] Wen et al 126 demonstrated direct microchannel isoelectric focusing (IEF)-MS using a chip constructed on polycarbonate plates for the characterization of protein mixtures. Zhang et al 93 designed a microdevice from glass wafers, which integrated a guiding channel for insertion of the electrospray capillary.…”
Section: Ce-ms In Microfabricated Devicesmentioning
confidence: 99%
“…Zhu et al 79 utilized CE-ESI-MS and MALDI-MS mapping to obtain high sequence coverage (up to 100% for small proteins and up to 90% for larger ones) of proteins from breast cancer cells. Li et al demonstrated the analytical potential of microdevices for identification of proteins from Haemophilus influenzae 127 and Neisseria meningitidis 129 using both peptide mass-fingerprint database searching and on-line tandem MS.…”
Section: ·1 Identification Of Proteinsmentioning
confidence: 99%